(untitled) (Research, Society and Development, 2022)
Aiming to achieve greater economic returns by increasing the biomass and productivity of strategic crops, such as soybeans, this article aimed to evaluate the efficiency of TrichoPlus (Trichoderma asperellum), as a promoter of plant growth in soybeans. Four independent experiments were carried out in the municipalities of Porto Nacional and Gurupi, Tocantins, Brazil, in the 2017/2018 and 2018/2019 harvests. Four experiments were conducted, each with four treatments with different doses of TrichoPlus (2, 3, 4 and 5 g kg-1 per seeds), plus two control treatments, one positive control with commercial product based on Trichoderma asperellum and one absolute control (without inoculation). For the treatment with the TrichoPlus product, the powder formulation was used, with active ingredient based on Trichoderma asperellum 201, formulated with a minimum concentration of 2 x 108 CFU g-1. The positive results for the biomass characteristics, stand maintenance and productivity were evidenced in the different doses of TrichoPlus, with emphasis on doses close to 5 g kg-1 of seeds, with gains in productivity above 23% for the 2017/2018 harvest and above 9% for the 2018/2019 harvest in Gurupi. In Porto Nacional the productivity gain for the 2017/2018 harvest was over 21% and for the 2018/2019 harvest it was over 27% in relation to the absolute control. Considering the different doses of TrichoPlus used in the experiments, there were differences between the doses with the best results for treatments with doses of 4 and 5 g kg-1 of seeds.